FAMILY-PARENT-NEW PLACE COOPERATION IN THE EDUCATION OF CHILDREN WITH DEVIANT BEHAVIOR (World Bulletin of Education and Learning, 2026)
This article analyzes the content, importance and directions of cooperation between the family, parents and local institutions in the education of children with deviant behavior. The need to strengthen the integral connection between moral values in society, the family environment, local control and the education system is highlighted. The article presents scientific views on the causes of deviant behavior, mechanisms for its prevention and the impact of the social environment on the child's personality.Keywords:deviant behavior, family, parents, local community, social control, cooperation, personality, upbringing, prevention.
Keywords: Deviant behavior, family upbringing, parenting responsibility, mahalla institution, community-based social control, prevention mechanisms, school–family–mahalla partnership, socialization and moral education.